Marker assisted identification of improved restorer lines with yield enhancing genes adaptable for aerobic conditions - Kadthala, Bhargava; D, Shivani; SNCVL, Pushpavalli; P, Beulah; P, Sadhana; RM, Sundaram; P, Senguttuvel (ORYZA-An International Journal of Rice, 2024)
To feed the world's growing population, development and introduction of climate resilient rice varieties/hybrids with increased yield ability are the need of the hour. This can be accomplished through novel genetic approaches such as hybrid rice technology, using a diverse set of parental lines with high restoring ability and specific desirable traits. In our study, for perse genetic yield improvement in aerobic restorer line AR 9-18R, hybridization was carried out with yield enhancing donor YPK 198 possessing Gn1a and OsSPL14 during kharif, 2018 and generated F1s were fixed for its hybridity through morphological and molecular analysis. In kharif, 2019 two hundred and five F2 population obtained were screened for two yield-enhancing Gn1a and OsSPL14 genes along with two fertility restorer genes Rf3 and Rf4 at ICAR-IIRR, Hyderabad. c2 analysis revealed that the c2 value of both yield enhancing genes was non-significant as the population was segregated in a ratio of 1:2:1. whereas c2 value for fertility restorer genes was significant as population deviated from 1:2:1. Phenotypic evaluation of F2 population for yield related traits exhibited high GCV and PCV for number of productive tillers, number of grains per panicle and single plant yield. Plant height, number of productive tillers, number of grains per panicle and single plant yield displayed high heritability along with high genetic advance as per cent of mean. Correlation and path co-efficient analysis revealed that plant height, number of productive tillers and number of grains per panicle are very important traits as selection criteria for effective yield improvement.